Ein neuer Papyrus aus dem Dossier des comes Johannes - Kramer, Bärbel; Hagedorn, Dieter (De Gruyter, 2010)
Abstract: Edition of a new papyrus from the dossier of the comes Johannes, containing the order of the comes to Philoxenos, manager of a hamlet or estate called Peribleptou, to supply 12 nomismatia for the purchase of reed for the vineyard and 4 nomismatia for bulls.
Aus: Archiv für Papyrusforschung und verwandte Gebiete, 56 (6 July 2010), Nr. 1. pp. 59-63. ISSN 1867-1551